(untitled) (Bangladesh Journal of Otorhinolaryngology, 2024)
Background: Pyogenic granuloma is a rapidly growing benign fibrovascular lesion involving the skin and mucous membranes. It usually affects the head and neck regions. The most common site is the oral cavity, while involvement of the nasal cavity is quite rare. Though few cases in the nasal cavity have been reported, occurrence in the inferior turbinates is extremely rare. The exact aetiology is unknown. It is often associated with pregnancy. Microtrauma, hormonal changes, and contraceptives may be the causative factors for the development of this vascular mass. Case report: Here we present the case of a 28-year-old woman, 2 weeks postpartum, with epistaxis and nasal obstruction. Diagnostic nasal endoscopy revealed a vascular mass arising from the right inferior turbinate. The patient was treated successfully by endoscopic excision of the mass. Conclusion: Pyogenic granuloma should be considered as a differential diagnosis in any pregnant woman presenting with a vascular mass in the head and neck region. Bangladesh J Otorhinolaryngol 2024; 30(1): 34-38